Representasi Trauma Novel “Aku Tak Membenci Hujan” Karya Sri Puji Hartini: Kajian Psikologi Sastra Cathy Caruth - Malika Zuhrotun Nisak; Syamsul Sodiq (CV. SINAR HOWUHOWU, 2026)
This study aims to describe the forms of trauma experienced by the character Karang and the development process of the trauma until the process of walking through. The method used in this study is a qualitative descriptive method. The research data source is the novel